Genetic variation at the CD28 locus and its impact on expansion of pro-inflammatory CD28 negative T cells in healthy individuals - Evaggelia Liaskou (Nature Portfolio, 2017)
Abstract The CD28 locus is associated with susceptibility to a variety of autoimmune and immune-mediated inflammatory diseases including primary sclerosing cholangitis (PSC). Previously, we linked the CD28 pathway in PSC disease pathology and found that vitamin D could maintain CD28 expression. Here, we assessed whether the PSC-associated CD28 risk variant A (rs7426056) affects CD28 expression and T cell function in healthy individuals (n = 14 AA, n = 14 AG, n = 14 GG). Homozygotes for the PSC disease risk allele (AA) showed significantly lower CD28 mRNA expression ex-vivo than either GG or AG (p < 0.001) in total peripheral blood mononuclear cells. However, the CD28 risk variant alone was not sufficient to explain CD28 protein loss on CD4+ T cells. All genotypes responded equally to vitamin D as indicated by induction of a regulatory phenotype and an increased anti-inflammatory/pro-inflammatory cytokine ratio. A genotypic effect on response to TNFα stimuli was detected, which was inhibited by vitamin D. Together our results show: (a) an altered gene expression in carriers of the susceptible CD28 variant, (b) no differences in protein levels on CD4+ T cells, and (c) a protective effect of the variant upon CD28 protein loss on CD4+ T cells under inflammatory conditions.